Living in the shadow of unemployment -an unhealthy life situation: a qualitative study of young people from leaving school until early adult life - Anne Hammarström; Christina Ahlgren (BMC Public Health, 2019)
Abstract Background Despite the magnitude of youth unemployment there is a lack of studies, which explore the relations between health experiences and labour market position in various contexts. The aim of this paper was to analyse health experiences among young people in NEET (not in education, employment or training) in relation to labour market position from leaving school until early adult life. Method The population consists of everyone (six women, eight men) who became unemployed directly after leaving compulsory school in a town in Northern Sweden. Repeated personal interviews were performed from age 16 until age 33. The interviews were analysed using qualitative content analysis. Results Health experiences can be viewed as a contextual process, related to the different phases of leaving school, entering the labour market, becoming unemployed and becoming employed. Perceived relief and hope were related to leaving compulsory school, while entering the labour market was related to setbacks and disappointments as well as both health-deteriorating and health-promoting experiences depending on the actual labour market position. Our overarching theme of “Living in the shadow of unemployment – an unhealthy life situation” implies that it is not only the actual situation of being unemployed that is problematic but that the other phases are also coloured by earlier experiences of unemployment . Conclusion A focus on young people’s health experiences of transitions from school into the labour market brings a new focus on the importance of macroeconomic influence on social processes and contextualised mechanisms from a life-course perspective.